Experimental maturation of Archaea encrusted by Fe-phosphates. Issue 1 (December 2017) - Miot, J.; Bernard, S.; Bourreau, M.; Guyot, F.; Kish, A.
Abstract Burial is generally detrimental to the preservation of biological signals. It has often been assumed that (bio)mineral-encrusted microorganisms are more resistant to burial-induced degradation than non-encrusted ones over geological timescales. For the present study, we submittedSulfolobus acidocaldarius experimentally encrusted by amorphous Fe phosphates to constrained temperature conditions (150 °C) under pressure for 1 to 5 days, thereby simulating burial-induced processes. We document the molecular and mineralogical evolution of these assemblages down to the sub-micrometer scale using X-ray diffraction, scanning and transmission electron microscopies and synchrotron-based X-ray absorption near edge structure spectroscopy at the carbon K-edge. The present results demonstrate that the presence of Fe-phosphates enhances the chemical degradation of microbial organic matter. While Fe-phosphates remained amorphous in abiotic controls, crystalline lipscombite (FeII x FeIII 3−x (PO4 )2 (OH)3−x ) entrapping organic matter formed in the presence ofS. acidocaldarius cells. Lipscombite textures (framboidal vs. bipyramidal) appeared only controlled by the initial level of encrustation of the cells, suggesting that the initial organic matter to mineral ratio influences the competition between nucleation and crystal growth. Altogether these results highlight the important interplay between minerals and organic matter during fossilization, which should be taken into account when interpreting the fossil record.